Primary Angiosarcoma of Urinary Bladder: 13th Reported Patient - Zaher Bahouth; Ismael Masarwa; Sarel Halachmi; Ofer Nativ (Case Reports in Oncological Medicine)
Angiosarcoma of the urinary bladder is an extremely rare and poorly characterized tumor. We are presenting the 13th reported patient who was an 89-year-old man initially presented with massive hematuria. His past medical history included external-beam radiation for prostate cancer 12 years ago. His PSA was 0.26 ng/dL. His CT-Urography demonstrated a highly vascular mass originating from the bladder base. The mass was partially resected, transurethrally. The pathology was consistent with primary angiosarcoma of the urinary bladder. Bone scan and CT-U showed metastasis to spine. The patient was treated with palliative radiotherapy for back pain due to metastasis, and he refused chemotherapy. The patient died 3 months after his initial diagnosis.